Atlas : multiple sclerosis resources in the world, 2008. - Dua, Tarun; Rompani, Paul (World Health Organization, 2008)
This publication from the World Health Organization and the Multiple Sclerosis International Federation (MSIF) presents evidence on the global epidemiology of multiple sclerosis and the resources to diagnose, treat, rehabilitate, support and provide services to people with MS. It summarizes information from 112 countries, representing 88% of the global population, thus can be considered as the leading global assessment on multiple sclerosis. The results of the survey reveal a lack of services and resources allocated to the care of people with MS. The situation is of particular concern in most low and middle income countries.--Publisher's description.